The right to be offline as a fundamental right of employees working remotely - Olejnik, Katarzyna (Undesirable Phenomena in Employment from the Perspective of Labour Law - Selected Issues, 2023)
More than three years ago, the world faced the COVID-19 pandemic. Most of the world’s countries have united to jointly counteract the spread of the SARS-CoV-2 virus. Many mandatory and optional solutions have been introduced to contain the pandemic. One of them was the recommendation addressed to employers to instruct employees – if possible – to work remotely (so-called home office). This allowed a large number of people to stay at home, which was supposed to minimize the risk of getting sick. Over time, this solution has become widely used as an alternative to traditional work, i.e. stationary work at the employer’s premises. While home-office working is intended to benefit both employers and employees, it is not without its disadvantages. These include, among others, the problem of protecting the employee’s privacy or his or her working time, especially with regard to the protection of his or her free time. The main part of the study will focus on the premises for the implementation of the right to be offline. The research methods used in the following study will be the literaturę analysis method and the formal-dogmatic method.